Teaching information literacy : 50 standards-based exercises for college students - Burkhardt, Joanna M.; MacDonald, Mary C.; Rathemacher, Adree J. (American Library Association, 2010)
"Covering the basics of planning, collecting, and evaluating, each of the 50 standards-based exercises in this book address one or more of the ACRL Information Literacy Competency Standards for Higher Education and promote conceptual and applied skills via active learning, problem-based learning, and resource-based learning."--[back cover]